Harmonizing Voices: Democratic Public Sphere in Nepal - Saemah Sahmin (Epistemik Press, 2024)
The purpose of this study is to investigate the significance of the democratic public realm on people' civic development. Citizenship and democracy are intertwined and interdependent. Democracy is a system designed to prioritize the will of the people, or citizens. Citizenship is also described as an act of citizenship (civic engagement) that fosters critical thinking, democratic activities, and participation since citizenship itself is always connected with successful democratic citizens. This research approach uses case studies to investigate democratic public principles in a comprehensive manner. The study comes to the conclusion that a vital forum for addressing social concerns and encouraging community involvement is the democratic public sphere. It also helps people absorb important principles of civil society, such as collaboration, diversity, tolerance, and politeness. Through encouraging tolerance and fraternal ideas in the neighborhood, nation, and state, this democratic and participatory arena cultivates a peaceful atmosphere.